Reprecipitation of poorly water-soluble cilostazol crystals using adsorbing carriers for enhanced dissolution and physicochemical modification - Baek, Namhyun; Oh, Ga Hui; Park, Chulhun; Tran, Thuy Thi Thanh; Park, Young Joon; Oh, Euichaul; Le, Hau; Tran, Thao T.D.; Park, Jun Bom; Lee, Beom Jin (Journal of Drug Delivery Science and Technology, 2018)
The aim of this new work was to improve the dissolution rate of poorly water-soluble cilostazol (CLT) by adsorbing dissolved drug molecules onto the surface of undissolved carriers via reprecipitation and deposition process as the solvent (methylene chloride) was evaporated. The adsorption mixtures of CLT with Aerosil 300 and lactose monohydrate provided better drug dissolution rate as compared to mannitol. However, Aerosil-based adsorption powders were unable to be compressed into tablet due to low and unsatisfactory compressibility. The optimized CLT-loaded tablets containing lactose-based adsorption powders displayed almost complete dissolution within 90 min and showed significantly higher dissolution in intestinal fluid (pH 6.8) containing 0.2% sodium lauryl sulfate than the control tablet and the commercial reference product Pletaal® (Otsuka). Differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) indicated that the crystalline property of CLT remained in adsorption powders with diminutive peak intensity. Fourier transform infrared spectroscopy (FT-IR) spectra indicated that the intermolecular hydrogen bond was formed between drug molecule and lactose monohydrate. Field-emission scanning electron microscope (Fe-SEM) clearly confirmed that CLT crystals with reduced size around 10 μm were adsorbed and deposited onto the surface of adsorbent material.
Keywords: Adsorbing carriers; Enhanced dissolution; Intermolecular hydrogen bond; Micromeritics; Poorly water-soluble cilostazol; Reprecipitation of dissolved drug crystals